Topical issues of the content of the legal culture (Journal of actual problems of jurisprudence, 2018)
This article analyzes the legal culture of civil society. The aim of the paper is the selection of values of legal culture of the Republic of Kazakhstan in the development of a democratic state. In the article the essence and structure of legal culture and its features. Particular attention is given to studying the legal aspects of the cultural values of the Republic of Kazakhstan in the development of a democratic state and civil society formation. In addition, we studied the main approaches to the understanding of the legal culture. Scientific work is based on the research of Kazakhstani and foreign authors on the nature of law and legal culture, its valuable reference in the formation of civil society and the rule of law in the Republic of Kazakhstan. It concludes that the main principle of civil society advocates free and comprehensive development of the individual in society, and that civil society starts with the appearance of the citizen as a free member of society who is aware of its purpose, endowed with a set of rights and freedom and the duty of responsibility for their actions to the society.Key words: legal culture, democratic state and its values, civil society, nature of legal reforms of Kazakhstan, absolute values of the human personality.